A Multi-Modal Energy Harvesting Device for Multi-Directional and Low-Frequency Wave Energy - Zhu, Yikai; Yang, Zhou; Jiao, Chong; Ma, Mengchao; Zhong, Xiang (Frontiers in Materials, 2022)
As a kind of sustainable energy source, ocean wave energy has always attracted attention. Because of the characteristics of multi-directions and low-bandwidth, the harvesting of wave energy has always been difficult. To harvest broadband wave energy in multiple directions and improve power generation efficiency, we present a multi-modal energy harvesting device by using a cross beam structure. In this device, the efficient harvesting of multi-frequency vibration energy in multiple directions has been achieved by using the multi-modal characteristics of the structure and the high power generation efficiency of the electric device based on liquid metal. Contrast experiments in multiple directions show that the device not only has the capability of multi-directional energy harvesting but also can work in the sweep range of the full band. Under horizontal excitation, compared with traditional single cantilever structure, the peak power density increased to 2227% and the working frequency band increased to 6.25 times. The experimental results show that the device significantly improves the efficiency of low-bandwidth multi-directional energy harvesting, providing a new method for vibration energy harvesting.